PEMANFAATAN TANAMAN OBAT OLEH MASYARAKAT DI SEKITAR HUTAN DESA SEMANDANG KIRI KECAMATAN SIMPANG HULU KABUPATEN KETAPANG - Julio, Yulius Rio; Idham, M; Oramahi, H A (JURNAL HUTAN LESTARI, 2019)
Medicinal plants are one of the important components in medicine, which are traditional herbal remedies and have been used since hundreds of years ago, to solve various health problems it faces. Therefore traditional medicine needs to be nurtured, cared for and preserved, because it is a wealth of Indonesian culture. This study aims to obtain data on the number and type of medicinal plants as well as the use of medicinal plants, among others, how to mix medicinal ingredients, how to treat them and their efficacy by the people in Semandang Kiri Village, Simpang Hulu Subdistrict, Ketapang Regency. The benefits of this study are expected to be able to take action to preserve the existence of traditional medicinal plants so that they can be utilized optimally and sustainably by the people in the Semandang left village in the upstream intersection of Ketapang Regency, and can provide useful information on medicinal plants. This research is descriptive in nature using the snowball sampling technique or carried out sequentially by asking for information on the person interviewed or contacted beforehand. Based on the results of research on the types of medicinal plants used by communities around the Semandang Kiri village, the upstream intersection of Ketapang District, 56 species of medicinal plants were found in 38 families and the use of medicinal plants most utilized from 56 species.Keywords: Medicinal plants, utilization, traditional medicine